Ramadan in the garden of knowledge and virtue - Abdul Razak, Dzulkifli (New Straits Times Press (M) Bhd., 2019)
Knowledge has always been likened to a tree with its many branches representing the many disciplines of knowledge, some bearing fruits and flowers. the soul of education is to recognise what “virtue” is all about. For virtue is the root of the tree, so to speak; the unseen part underneath a tree that gives rise to the whole tree. the whole person whom the Quran likened to a “good” tree, and the virtue that is rooted therein. There is no tree without roots (except for “artificial” ones) and in fact the latter determines the quality of the former.